A novel variation of the recurrent laryngeal nerve - Wu, Gaosong (BMC Surg, 2017)
BACKGROUND: Injury to the recurrent laryngeal nerve is one of the most severe complications of thyroid surgery. Several anatomic variations of the nerve increase the likelihood of iatrogenic damage. CASE PRESENTATION: A 50-year-old woman was presented to our department with a nodule in the right thyroid lobe, and she reported no voice changes. She had no history of surgery or radiation to the head or neck. Fine-needle aspiration was recorded as papillary thyroid carcinoma. The preoperative laryngoscopy revealed left vocal cord paralysis. Right thyroid lobectomy was performed. A scarce course of the left recurrent laryngeal nerve was found during the operation that ascended along the medial edge of the superior thyroid pole and finally disappeared beneath the superior cornu of the thyroid cartilage without any tracheal, esophageal, or laryngeal branches. The patient was discharged on the third postoperative day with the diagnoses of papillary thyroid carcinoma and congenital left vocal cord paralysis. CONCLUSIONS: The novel variation of the recurrent laryngeal nerve may challenge the current concept of the anatomy of the nerve. The vocal folds mobility should be examined routinely before surgery in patients undergoing thyroid operation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12893-017-0263-5) contains supplementary material, which is available to authorized users.